HUBUNGAN KEJADIAN PENYAKIT INFEKSI TERHADAP KEJADIAN STUNTING PADA BALITA 1-4 TAHUN - Angina Rohdalya Solin; Oswati Hasanah; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Stunting (short) is the late growth of children which results in not reaching normal height, this is influenced by the presence of chronic nutritional problems, both in the mother / prospective mother during the fetus, nutrition at the age of infants / toddlers and infectious diseases suffered during infancy. The aim of the study was to see the relationship between the incidence of infectious diseases and the incidence of stunting in infants. This research was conducted at the Pekanbaru Rejosari Health Center with a descriptive correlation design study using a retrospective approach. The research sample was taken by accidental sampling on 30 respondents. The sample inclusion criteria were toddlers aged 1-4 years, toddlers who visited the Rejosari Health Center. The measuring instrument used is the meter and anthropometric table of the Indonesian Ministry of Health and a questionnaire about the frequency of diarrhea and ISPA that has been tested for validity and reliability. The statistical test results of diarrheal infectious disease on stunting events using the Chi-Square test obtained p value (0,000) < (α = 0.05) and the results of statistical tests for the incidence of ISPA infection against stunting events were obtained p value (0.001) <(α = 0.05) showed that there was a relationship between diarrheal infectious disease and ISPA in the incidence of stunting in infants with the results expected by the government to have a real effort on the health of children under five, to improve good nutrition and treatment for sick children in order to avoid infectious diseases which caused toddlers are left to experience infectious diseases for a long time.Keywords: Acute Respiratory Tract Infection (ISPA), Diarrhea, Infectious Disease and Stunting